Integration of Pixton and Deep Learning in Teaching Descriptive Writing in German: A Conceptual-Case Study Hybrid: Integrasi Pixton dan Deep Learning dalam Pengajaran Menulis Deskriptif dalam Bahasa Jerman: Hibrid Studi Kasus Konseptual - Wahyuni, Tri; Darni; Resdianto Permata Raharjo (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This article explores the integration of Pixton, a digital comic creation platform, with deep learning principles to enhance descriptive writing skills in German among Indonesian high school students. The study addresses the persistent challenges of low motivation and limited proficiency in descriptive writing by developing and implementing a Pixton-based teaching module grounded in mindful, meaningful, and joyful learning. Employing a conceptual and case study approach, the research involved needs analysis, module design using the ADDIE model, classroom implementation with 12th-grade students at SMAN 1 Driyorejo Gresik, and qualitative evaluation through observations, interviews, and reflections. Results indicate that the module increased student engagement, creativity, and collaboration, as well as improved vocabulary and sentence structure in German writing. However, challenges such as limited access to technology and the need for teacher training were identified. The findings highlight the potential of combining digital tools and deep learning to create engaging, student-centered language learning experiences.